Development of Novel Passive Control Techniques for More Uniform Temperature at Combustor Exit and Hybrid Les/Rans Modeling - (:unkn) unknown (My University, 2014)
Gas turbines have become an important, widespread, and reliable device in the field of power generation. For any gas turbine system, the combustor is an integral part responsible for the combustion of the fuel. A number of studies have shown that the flow field exiting a combustor is highly non-uniform in pressure, velocity and, most importantly, temperature. Hot streaks amongst other non-uniformities cause varying thermal stresses on turbine blades and put pressure on the blade materials. In particular, these non-uniformities can have detrimental effects on the performance of the engine and cause a reduction in the expected life of critical components such as the turbine vanes. Due to the importance and severity of the problem, a large portion of the total combustor development effort is devoted to achieving better temperature uniformity. The present work is another attempt to develop novel passive control techniques to enhance mixing in a facility simulating the dilution zone of a typical gas turbine combustor and produce more uniform temperature at the combustor exit. Extensive experimentation was conducted to compare the proposed dilution techniques - staggered dilution holes, staggered dilution holes with streamlined body and staggered dilution holes with guide vanes at various orientations (0°, 30°, 60° and 90°). A weighted parameter was defined called `uniformity factor ('χ^' ) to compare how close the mixture fraction is to the equilibrium value. For the majority of the flow conditions tested, the 30° guide vanes gave the most uniform temperature flow with just about 2% higher pressure loss as compared to the staggered dilution holes geometry. The fact that the use of 30° guide vanes can provide the turbine blade with 15% more uniform temperature flow than the staggered dilution holes design with merely 2% more pressure drop, has a very important implementation in order to reduce the damage of the turbine blades due to non-uniform temperature flow and extend its life-span. This would result in an overall reduction in the maintenance cost of the gas turbine systems which is quite significant. Furthermore, it was found that the introduction of the streamlined body not only improved the mixing in some cases but also helped decrease the pressure drop from inlet to exit of the experimental set-up. This is expected to increase the overall system efficiency and decrease the operating cost of a gas turbine system. Additionally, numerical modeling was used for various parametric studies to explore the effect of jet-to-mainstream momentum flux ratio on the exit temperature uniformity, variation of the cooling rate within the dilution zone, exergy analysis, etc. The other significant part of this work comprised of development of an Algebraic Stress Model (ASM) in order to estimate the turbulence via Reynolds stresses prediction. The ASM model developed is validated for a simple two-dimensional turbulent flow over a flat plate and a complex three dimensional flow around Ahmed body. The developed model is capable of predicting Reynolds stresses for a variety of flow regimes. Based on these validation it can be concluded that adopting a hybrid approach which combines the advantages of the ASM model with other turbulence models can be sought after for a more in-depth analysis of the flow structures and turbulent quantities both near-wall and away from the boundary for any fluid flow problem. The accurate prediction of the turbulent quantities plays a significant role in not just the fluid motion/transfer phenomenon rather it governs the heat exchange process as well especially in regions close to the wall.
Keywords: Algebraic Stress Model; Combustor; Experiment; Mixture Fraction; Temperature; Turbulence Modeling